Kesulitan-Kesulitan Mahasiswa dalam Memahami Novel Inggris: Suatu Kajian - Firdiansyah Firdiansyah (Universitas Batanghari Jambi, 2022)
This article discusses about students’ difficulties in comprehending English novel at English Literature department of UIN Sulthan Thaha Saifuddin Jambi. The researcher analyse this article by using qualitative design. The data are collected by using documentation technique and interview technique. The interview is conducted with ten students that are selected based on purposive sampling. Then, the data are analysed by using descriptive analysis technique. The result of this analysis shows that the students’ difficulties in comprehending English novel are lack of vocabulary and lack of grammar understanding.